2007
DOI: 10.1098/rsta.2006.1999
|View full text |Cite
|
Sign up to set email alerts
|

Messages from GRB 060218

Abstract: GRB 060218 is a watershed event. Statistically, its detection suggests that there is likely a distinct low-luminosity (LL) population of gamma-ray bursts (GRBs) whose event rate is much higher than that of conventional high-luminosity GRBs. This LL population may give significant contribution to the diffuse neutrino background flux at energies higher than 10 16 eV. The spectral lag of this burst is very long, and roughly follows the luminosity-lag relation of normal GRBs. This, along with the fact that it foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…We then take an constant medium density (n). The temporal evolution of both minimum and cooling frequencies (ν m and ν c ) in the reverse and forward shock regions are taken from Rossi et al (2003), Fan et al (2006), Zhang et al (2007) and Yi et al (2013).…”
Section: Theoretically Modeling the Afterglow Lightcurvesmentioning
confidence: 99%
“…We then take an constant medium density (n). The temporal evolution of both minimum and cooling frequencies (ν m and ν c ) in the reverse and forward shock regions are taken from Rossi et al (2003), Fan et al (2006), Zhang et al (2007) and Yi et al (2013).…”
Section: Theoretically Modeling the Afterglow Lightcurvesmentioning
confidence: 99%
“…Results indicate considerably more complexity in many bursts than would be expected from the standard fireball model and varying degrees of correspondence between the X-ray and the optical light curves. In this respect, GRB 050525A may be an exception as it exhibits an achromatic jet break at w10 4 s, although, even in this case, the decay indices are shallow compared with what might be expected from the standard model (Zhang et al 2007; and references therein). Afterglow behaviour from other bursts is not so easily interpreted and the absence of jet breaks in the X-ray afterglow, when present in the optical, remains to be understood.…”
Section: Afterglowsmentioning
confidence: 87%
“…Swift's multi-wavelength measurements (gamma ray to optical/UV) of the exceptional nearby burst GRB 060218 (zZ0.033) have provided a direct observation of the shock breakout in a supernova collapse (Campana et al 2006;Blustin 2007;Zhang et al 2007), this observation adding to the small sample of previously observed nearby long GRBs associated with supernova collapse. Conversely, Swift has found two bursts, GRB 060614 and GRB 060505, for which no supernova association has been found down to deep limits (Watson et al 2007;and references therein).…”
Section: Observational Contributions From Swiftmentioning
confidence: 98%
“…We then adopt a constant medium density (n). The temporal evolution of both the minimum and cooling frequencies (ν m and ν c ) in the RS and FS regions are taken from Yost et al (2003); Fan & Piran (2006); Zhang et al (2007a), and Yi et al (2013). The model does not incorporate emission produced by the inverse-Compton effect, which is expected to delay the transition between the fast and slow cooling phases, as well as to decrease the cooling frequency in the FS (Wu et al 2005).…”
Section: Model Fitmentioning
confidence: 99%